TEORI-TEORI HUKUM KONTRAK BERSUMBER DARI PAHAM INDIVIDUALISME - Saptono, Saptono (REPERTORIUM, 2014)
AbstractThis paper analyzes the problem about how the ideology of individualism in the freedom of contract and whatÂ kind of theory that comes from the idea of individualism in the freedom of contract. To examine the issue, thisÂ paper using a normative assesment, the study of literature and legal materials. The result show that, first, theÂ individualâs autonomy is the basis of freedom of contract which became the foundation for the developmentÂ of contract law. Second, the individual theory which is source from the will theory or the classical theory ofÂ contract law that derived from the principle of private autonomy, namely that the will of parties to determineÂ their contractual legal relationship.Â Abstrak:Tulisan ini menganalisis tentang bagaimana ideologi individualisme dalam kebebasan berkontrak, dan teoriÂ apa saja yang bersumber dari paham individualisme dalam kebebasan berkontrak tersebut. Untuk mengkajiÂ permasalahan tersebut, tulisan ini menggunakan metode yuridis normatif, dengan studi kepustakaan dan bahan-bahan hukum. Kesimpulan yang dapat diambil yakni pertama, otonomi individu menjadi dasar kebebasanÂ berkontrak Â yang kemudian menjadi landasan bagi perkembangan hukum kontrak. Yang kedua, teori yangÂ bersumber dari paham individualisme yaitu teori kehendak atau teori hukum kontrak klasik yang berasal dariÂ prinsip otonomi individu, yakni kehendak para pihak menentukan hubungan klasik mereka.Â